Figure 27. Varieties of Sea-Weed Used to Produce Varech - Appleton, John Howard (Chemistry, Developed by Facts and Principles Drawn Chiefly from the Non-Metals, 1884)
Black and white illustration depicting several varieties of sea-weed used to produce varech, also known as kelp. The accompanying text describes various applications of sea-weed, including as a fertilizer and source of alkali. This plate is from John Howard Appleton's (1844-1930) Chemistry, Developed by Facts and Principles Drawn Chiefly from the Non-Metals, published in 1884. Intended as an introduction to the study of chemistry, this volume contains illustrations throughout the text including color plates. Color plates have been digitized along with a selection of illustrations.
Keywords: Textbooks; Science--Study and teaching; Marine algae; Scientific illustration; Marine plants